A Study of Formative Assessment Implementation through Classroom Interactional Competence: Discourse Analysis in English Classes at Lalian Atambua Seminary Senior High School - Bajo, Simforianus Mario; Hornay, Priscilla Maria Assis; Erfiani, Yohanes P. F. (Universitas Pahlawan Tuanku Tambusai, 2026)
This qualitative case study investigates the role of teachers’ Classroom Interactional Competence (CIC) in the implementation of formative assessment in English lessons at a senior high school located in Indonesia’s 3T (frontier, outermost, and disadvantaged) region. While previous Indonesian studies have primarily relied on survey and self-report data, little attention has been paid to how formative assessment is enacted through naturally occurring classroom interaction, particularly in marginalised contexts. Using Classroom Discourse Analysis informed by Conversation Analysis principles, two complete lessons taught by one experienced teacher, purposively selected as an information-rich case, to Grade XI students (N = 52) at SMA Seminari Lalian Atambua, Belu Regency, East Nusa Tenggara, were audio-recorded and transcribed to capture recurring interactional patterns through detailed, turn-by-turn analysis. Findings reveal that classroom interaction was heavily dominated by the traditional IRF/E pattern, with display questions comprising 23.8% of teacher turns and advanced CIC practices (referential questions, extended wait time, clarification requests, confirmation checks, and scaffolding) accounting for only 8.7%. In 24 identified formative assessment episodes, 83.3% of feedback moves were evaluative or effusive praise that closed sequences without guiding improvement, while scaffolded, suggestive feedback occurred only once (4.2%) yet produced immediate and extended student uptake. The results confirm that, in this severely under-resourced context, limited CIC transforms potentially formative moments into ceremonial, teacher-centred checks, thereby constraining the effectiveness of formative assessment. The study highlights CIC as a critical equity issue in marginalised regions and calls for discourse-focused professional development to enable teachers to create genuine “space for learning” even under significant contextual constraints.